2007
DOI: 10.1086/512847
|View full text |Cite
|
Sign up to set email alerts
|

The Nuclear to Host Galaxy Relation of High‐Redshift Quasars

Abstract: We present near-infrared imaging of the host galaxies of low-luminosity quasars at 1 < z < 2, aimed at investigating the relationship between the nuclear and host-galaxy luminosities at high redshift. This work complements our previous study to trace the cosmological evolution of the host galaxies of high-luminosity quasars. The sample consists of nine radio-loud (RLQ) and six radio-quiet (RQQ) low-luminosity quasars. They have similar redshift and optical luminosity distributions, and together with the high-l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
63
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(71 citation statements)
references
References 50 publications
(118 reference statements)
8
63
0
Order By: Relevance
“…At high redshift, the host galaxies appear to be consistent with elliptical morphologies Hyvönen et al 2007;Falomo et al 2004;Kotilainen et al 2007;Falomo et al 2008;Ammons et al 2009), despite the difficulties in constraining the types unambiguously. The merger fraction is <30%, not significantly different from field galaxies.…”
Section: Comparisons With Host Galaxy Morphology Studiesmentioning
confidence: 88%
“…At high redshift, the host galaxies appear to be consistent with elliptical morphologies Hyvönen et al 2007;Falomo et al 2004;Kotilainen et al 2007;Falomo et al 2008;Ammons et al 2009), despite the difficulties in constraining the types unambiguously. The merger fraction is <30%, not significantly different from field galaxies.…”
Section: Comparisons With Host Galaxy Morphology Studiesmentioning
confidence: 88%
“…For their z ≈ 1.5−2 sample they found a value of 9.78 ± 6.58 kpc for objects where it could be determined and upper limits (<10 kpc) for the remaining sources. Kotilainen et al (2007) found values of 6.7 ± 1.7 kpc for their z ≈ 1−2 sample (observed in K and H). Falomo et al (2008) found values between 2.6 kpc and 11.3 kpc for a sample of three high redshift quasars (z ≈ 2−3) observed in Ks.…”
Section: Host Galaxy Radiimentioning
confidence: 92%
“…Dunlop et al 2003;Percival et al 2001) up to very high redshifts of z ∼ 3 (e.g. Ridgway et al 2001;Falomo et al 2004Falomo et al , 2008Jahnke et al 2004;Kotilainen et al 2007). It is nowadays established that formation rates or ages of the host galaxy are difficult or even impossible.…”
Section: Introductionmentioning
confidence: 99%
“…They follow closely the correlation found between MBH and the host galaxy luminosity. Figure 10 plots the absolute R-band magnitudes of the quasar hosts versus those of their nuclei, as well as the Rband magnitudes as a function of redshift, for the AO sample as well as other quasars compiled by Kotilainen et al (2007) and Falomo et al (2008). In both plots, the four systems with robust host luminosities occupy the loci found for radio quiet quasars.…”
Section: Quasar Host Galaxies In the Ao Samplementioning
confidence: 98%